Penilaian Hasil Belajar Pendidikan Agama Islam: Penerapan Strategi, Skema, dan Alternatif Solusi di Tingkat Sekolah Dasar - Sibaweh, Imam (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This research aims to provide an assessment of Islamic Religious Education learning outcomes, which includes aspects of planning, objectives, types of evaluation, and implementation strategies. The approach used in this research is a qualitative approach with data collection carried out through interviews and literature analysis. The results of this research found that the evaluation of Islamic Religious Education learning achievement was designed to optimize efficiency and effectiveness, with an emphasis on 3 (three) assessment domains, namely: cognitive, affective and psychomotor. This allows educators to get a comprehensive picture of student learning outcomes and provide relevant feedback.